Progress in BazookaSPECT: High-Resolution, Dynamic Scintigraphy with Large-Area Imagers - Miller, Brian W. (Proc SPIE Int Soc Opt Eng, 2012)
We present recent progress in BazookaSPECT, a high-resolution, photon-counting gamma-ray detector. It is a new class of scintillation detector that combines columnar scintillators, image intensifiers, and CCD (charge-coupled device) or CMOS (complementary metal-oxide semiconductors) sensors for high-resolution imaging. A key feature of the BazookaSPECT paradigm is the capability to easily design custom detectors in terms of the desired intrinsic detector resolution and event detection rate. This capability is possible because scintillation light is optically amplified by the image intensifier prior to being imaging onto the CCD/CMOS sensor, thereby allowing practically any consumer-grade CCD/CMOS sensor to be used for gamma-ray imaging. Recent efforts have been made to increase the detector area by incorporating fiber-optic tapers between the scintillator and image intensifier, resulting in a 16× increase in detector area. These large-area BazookaSPECT detectors can be used for full-body imaging and we present preliminary results of their use as dynamic scintigraphy imagers for mice and rats. Also, we discuss ongoing and future developments in BazookaSPECT and the improved event-detection rate capability that is achieved using Graphics Processing Units (GPUs), multi-core processors, and new high-speed, USB 3.0 CMOS cameras.